2020
DOI: 10.1186/s12877-020-01798-z
|View full text |Cite
|
Sign up to set email alerts
|

Frailty as a predictor of future falls and disability: a four-year follow-up study of Chinese older adults

Abstract: Background Frailty, which is defined as aging-related multisystem impairments, can lead to adverse health outcomes. However, evidence for such a connection in Chinese older adults remains lacking. This study examined the association between frailty and future falls and disability among community-dwelling Chinese older adults. Methods Data were obtained from the 2011 and 2015 waves of the China Health and Retirement Longitudinal Study. Participants were aged 60 years and above at baseline in 2011 and complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…24 A prospective study by Zhang et al identified the frailer population was at risk of disability and falls in the future. 25 A similar association was also observed in the EPIDOS study in community-dwelling older adults using the phenotype model 26 and in the hospitalized patients by Liang et al…”
Section: Discussionsupporting
confidence: 74%
“…24 A prospective study by Zhang et al identified the frailer population was at risk of disability and falls in the future. 25 A similar association was also observed in the EPIDOS study in community-dwelling older adults using the phenotype model 26 and in the hospitalized patients by Liang et al…”
Section: Discussionsupporting
confidence: 74%
“…Our third theme considered psychological and social health. Depression and mental health problems was found to be associated with frailty in older Chinese (Chang et al 2011 ; Ma et al 2020 ; Tian et al 2018 ; Ye et al 2018 ; Zhang et al, 2020b ) and was an important contributor of frailty in the Singapore Longitudinal Ageing studies (Ng et al 2014 ). It has been suggested people with depression may be more pessimistic about the progression of their health problems, perceive less control over their objective health and foresees a poorer prognosis of their current health complaints (Hong et al 2004 , Taylor and Brown, 1988 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among others, frailty has already been studied as a measure able to predict palliative home care intensity [ 27 ]. Similarly, an association between frailty and disability has been observed [ 28 ], with the former showing extreme susceptibility and heightened vulnerability to adverse health outcomes, and the latter showing actual disabilities in carrying out daily activities. Together, those conditions, when severe, seem to require a sharp intensification of home palliative care visits and presumably lead to an increase in burden for caregivers.…”
Section: Discussionmentioning
confidence: 90%